And suddenly, the rain!: How surprises shape experienced utility - Paolo Figini; Veronica Leoni; Laura Vici (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
The utility associated with a service's consumption is contingent on its intrinsic characteristics and various situational factors. One key element that influences consumer satisfaction is adherence to prior expectations. This is particularly relevant for experience goods that highly depend on external factors, such as weather. On these premises, the current study explores the role of expectations on utility by analyzing the effect of weather surprises (i.e., the mismatch between forecast and realized weather) on online ratings. Results from the analysis of over 300,000 reviews posted on Booking.com indicate that weather surprises have an impact on the reported experienced utility, the effect depending on the sign of the surprise. Moreover, the consumption span moderates the surprise effect, thereby mitigating the impact of both positive and negative surprises on utility.
Keywords: D83; D91; L81; Q54; 330; weather bias; surprise effect; online reputation; experienced utility; online platforms